Synergistic effects of ball-milled biochar-supported exfoliated LDHs on phosphate adsorption: Insights into role of fine biochar support. (1st February 2022) - Li, Hangyu; Cui, Shihao; Tan, Yi; Peng, Yutao; Gao, Xing; Yang, Xiao; Ma, Yan; He, Xinyue; Fan, Beibei; Yang, Sen; Chen, Qing
Abstract: Although biochar supports were widely adopted to fabricate the biochar (BC) supported layered double hydroxides (LDHs) composites (LDH-BC) for efficient environmental remediation, few studies focus on the important role of biochar support in alleviating the stacking of LDHs and enhancing LDH-BC's performance. Through the analysis of the material structure-performance relationship, the "support effect" of fine biochar prepared by ball milling was carefully explored. Compared with the original LDHs on LDH-BC, the LDHs on ball milled biochar (LDH-BMBC) had smaller particle size (from 1123 nm to 586 nm), crystallite size (from 20.5 nm to 6.56 nm), more abundant O-containing functional groups, and larger surface area (370 m 2 g −1 ) and porous structure. The Langmuir model revealed that the maximum theoretical phosphate adsorption capacity of LDH-BMBC (56.2 mg P g −1 ) was significantly higher than that of LDH-BC (27.6 mg P g −1 ). The leaching experiment proved that the addition of LDH-BMBC in calcareous soil could significantly reduce the release of soil total phosphate (46.1%) and molybdate reactive phosphate (40.4%), even though pristine BC and BMBC significantly enhanced the soil phosphate leaching. This work fabricated high-performance and eco-friendly LDH-BMBC for phosphate adsorption in solution and phosphate retention in soil and also provide valuable insights into fine biochar support effect on LDHs exfoliation, extending the practical use of the engineered ball milled biochars in environment remediation.